Ecological aspects of South American Trypanosomiasis: XII - Regional variation of the Panstrongylus megistus domiciliary tred - Forattini, Oswaldo Paulo; Ferreira, Octávio Alves; Silva, Eduardo Olavo da Rocha e; Rabello, Ernesto Xavier (Revista de Saúde Pública, 1978)
The development of spontaneous colonies of Panstrongylus megistus in experimental fowlhouses showed regional variation with positive results in regions with an annual dry season, and negative ones in regions without this well-marked period. Beside this, the influence of the forest cover was suggested. Places with forest relics are shelters of the insect populations developing a higher ecological valence with a tendency to artificial ecotope invasion. Populations living in the more primitive and extensive forest environment of the Serra do Mar system seem to preserve mainly their wild behaviour, without a significant development of invasive power of artificial ecotopes. The association of this evidence, with primitive phytogeographic aspects, suggests that the dispersion center is the Serra do Mar system, from which the insect populations spread towards the west across South America. Man-made evironmental changes, mainly with forest destructions will probably enhance secondary adaptation to human dwellings. So, depending on the land utilization, the need of epidemiological surveillance should be emphasized.